Journal of Emergency and Disaster Medicine - Kassem, Abdel Meguid; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
The Journal of Emergency and Disaster Medicine focuses on research in medical and public health aspects of emergency and disaster medicine including preparedness, response, recovery, mitigation, and health policy making. The journal also includes research related to epidemics and pandemics of infectious diseases. Journal of Emergency and Disaster Medicine aims at disseminating high quality research and best practices in related topics and to support health policy makers in designing strategies and planning including resource allocation. Research on the implementation of technological advancements in prediction, prevention and management of medical disasters and in emergency medicine is of special interest.
Keywords: Emergency medicine; Public health; Emergency Medicine; Public Health